2008
DOI: 10.1029/2007gb003147
|View full text |Cite
|
Sign up to set email alerts
|

Simulated 21st century's increase in oceanic suboxia by CO2‐enhanced biotic carbon export

Abstract: The primary impacts of anthropogenic CO2 emissions on marine biogeochemical cycles predicted so far include ocean acidification, global warming induced shifts in biogeographical provinces, and a possible negative feedback on atmospheric CO2 levels by CO2‐fertilized biological production. Here we report a new potentially significant impact on the oxygen‐minimum zones of the tropical oceans. Using a model of global climate, ocean circulation, and biogeochemical cycling, we extrapolate mesocosm‐derived experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
263
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 259 publications
(285 citation statements)
references
References 39 publications
(56 reference statements)
18
263
4
Order By: Relevance
“…Hence, it appears too early to make a judgement on the sensitivity and longevity of this feedback. If there is a significant enhancement in the C:N drawdown at the surface that translates into an enhanced carbon export, it will lead to higher oxygen consumption and a possible expansion of oxygen-minimum zones (73), linking to the oxygen-related feedback described in Responses to Ocean Warming and Acidification. ⅐ Increased production of extracellular organic matter under high CO 2 levels (51) may enhance the formation of particle aggregates (74,75) and thereby increase the vertical flux of organic matter (negative feedback) (76).…”
Section: Impacts On the Biological Carbon Pumpsmentioning
confidence: 99%
“…Hence, it appears too early to make a judgement on the sensitivity and longevity of this feedback. If there is a significant enhancement in the C:N drawdown at the surface that translates into an enhanced carbon export, it will lead to higher oxygen consumption and a possible expansion of oxygen-minimum zones (73), linking to the oxygen-related feedback described in Responses to Ocean Warming and Acidification. ⅐ Increased production of extracellular organic matter under high CO 2 levels (51) may enhance the formation of particle aggregates (74,75) and thereby increase the vertical flux of organic matter (negative feedback) (76).…”
Section: Impacts On the Biological Carbon Pumpsmentioning
confidence: 99%
“…The UVIC2-8 model is the University of Victoria (UVic) Earth System Climate Model (Weaver et al, 2001) in the Redfield stoichiometry configuration described by Oschlies et al (2008). The oceanic component is a fully threedimensional primitive-equation model with nineteen levels in the vertical, ranging from 50 m thickness near the surface to 500 m in the deep ocean.…”
Section: A7 Uvic2-8mentioning
confidence: 99%
“…The authors attributed these changes to an increase in carbon overconsumption in the dominant phytoplankton groups and outlined the possibility of a more efficient carbon pump under future ocean conditions once this carbon-enriched POM sinks out of the surface ocean. Using a global biogeochemical model, Oschlies et al (2008) extrapolated these findings to the global ocean and found that the enhanced carbon export may lead to an expansion in suboxic water volume by up to 50% until the end of this century.…”
Section: Introductionmentioning
confidence: 99%